INCLUSIVE ECONOMY: THE FINANCIAL ASPECT OF DEVELOPMENT IN THE CONDITIONS OF GLOBALIZATION - GRON, Oleksandra; ARUTYUNYAN, Ovagim (Scientific journal «World of Finance», 2025)
Introduction. Currently, the world economy is experiencing rapid and significant changes that require new approaches to the development and management of economic systems. One of the important directions of these changes is the concept of an inclusive economy, which tries to ensure equal access to economic opportunities and resources for all members of society, including the least protected sections of the population. An inclusive economy aims to create the conditions under which economic growth and development are accessible and beneficial to all, not just privileged groups. In the conditions of globalization, the need to take into account the financial aspect of an inclusive economy becomes obvious. Global financial markets and institutions have a significant impact on resource allocation, access to capital, and economic opportunity. It is therefore important to consider how financial instruments, policies and strategies can be adapted to ensure greater economic and social inclusion. That is why the financial aspect of an inclusive economy covers access to financial services, including credit, investment, insurance and other financial instruments, which are critical to support economic participation and social integration. It also includes the development of financial policies that help reduce social inequality and improve the living conditions of all citizens. The purpose of the article is to substantiate the need to take into account the financial aspect of the development of an inclusive economy in the context of globalization. Results. The presented paper examines the main components of an inclusive economy, the role of globalization in the formation of the modern concept of an inclusive economy. The need to take into account the specifics of the financial aspect of the development of an inclusive economy in the context of globalization is also substantiated. A methodical approach to the development of an inclusive economy, taking into account the financial aspect, is proposed. Conclusions. The financial aspect of an inclusive economy is gaining particular importance in the context of globalization, when financial systems and markets are becoming more and more interconnected and complex. Globalization, on the one hand, opens up new opportunities for economic development and financial investment, and on the other hand, creates challenges that can increase inequality and social gaps. Analysis of the financial aspect of an inclusive economy in the context of globalization allows us to identify key problems and opportunities for improving financial access and equality. This includes assessing the impact of global financial trends on local economies, analyzing the effectiveness of financial instruments and policies, and developing recommendations for creating more inclusive financial systems. Thus, the study of the financial aspect of the inclusive economy in the context of globalization is important for the formation of strategies that will promote economic development, reduce social gaps and ensure sustainable and equal economic growth.